Pengenalan Huruf Hijaiyah Berbasis Augmented Reality Pada Taman Pendidikan Al-Qur’an - Audrey Hillary; Muhamad Azrino Gustalika; Yohani Setiya Rafika Nur (JURIKOM (Jurnal Riset Komputer), 2022)
The introduction of hijaiyah letters is only done manually using the Iqra 'book. The introduction is done by reading the letters and reciting them, so that the introduction process is still less interesting, especially for children who are just starting to learn the Qur'an and know the hijaiyah letters. An interactive learning is needed in the form of audio-visual so that children tend to be more responsive, one of the supporting factors for interactive learning is the existence of media or learning facilities that use mobile-learning (M-learning) technology. This study aims to introduce hijaiyah letters to children by using an application based on Augmented Reality technology, which can be operated using an Android smartphone. Data collection methods used in this study were observations and interviews conducted at the Al-Barokah Baturraden TPA. This research refers to the multimedia development method, namely the multimedia development life cycle (MDLC) as a system model in building applications. The output of this application is that the application will display a video on the smartphone screen containing the hijaiyah letter learning material. On the results of blackbox testing, namely functional testing, obtaining a percentage of 100%, which means the features in the application function properly in accordance with the design objectives. In usability testing using the usability scale system calculation, the score is 81.71 which means it gets an acceptable (high) category for acceptability or acceptance level, grade B for grade scale or application level and excellent rating for adjective rating or application rating which indicates that the application is acceptable. by the user. By using Augmented Reality-based applications, students can learn hijaiyah letters interactively and interestingly.